2021
DOI: 10.1080/23750472.2021.1986120
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and commitment of volunteers at parkrun events

Abstract: Purpose: Effective organisation and delivery of parkrun events are entirely reliant on the services provided by volunteers. We explore the motivations and commitment of volunteers who provide these services to further our understanding of volunteers at sport events.Research design: This study explores motivations and commitment to volunteer at weekly parkrun events in Worcester, UK. Data was collected from 92 participants using the Organisational Commitment Questionnaire (OCQ) and a motivation survey. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Therefore, the selected non-parametric test to carry out the study was the Mann-Whitney U test (Mann and Whitney 1947), as the sample was divided by gender into two independent subgroups, males and females. The Mann-Whitney U statistic has been successfully used for the same purpose in previous studies on sports events (Manzano-Sánchez et al 2020;Simplício-Barreto et al 2021;Renfree and West 2021). A null hypothesis was established for each item, consistent with no differences between males and females.…”
Section: Second Phase: Database Processingmentioning
confidence: 99%
“…Therefore, the selected non-parametric test to carry out the study was the Mann-Whitney U test (Mann and Whitney 1947), as the sample was divided by gender into two independent subgroups, males and females. The Mann-Whitney U statistic has been successfully used for the same purpose in previous studies on sports events (Manzano-Sánchez et al 2020;Simplício-Barreto et al 2021;Renfree and West 2021). A null hypothesis was established for each item, consistent with no differences between males and females.…”
Section: Second Phase: Database Processingmentioning
confidence: 99%
“…The reach and popularity of the parkrun phenomenon has stimulated a rich exploration in research, anchored in theoretical frameworks from sport and health (Reis et al, 2016;Renfree and West, 2019), and building community through sport . Early studies (Stevinson and Hickson, 2014) identified the public health potential, which was subsequently adopted by the UK Government as part of policy to build a more active nation (DCMS, 2015).…”
Section: Findings Phase 1: Parkrun Research Reviewmentioning
confidence: 99%
“…The engagement did not fully assess the effects of fundamental requirements on the flow state because the requirements for autonomy and competence may predict the flow state. Sport researchers have routinely investigated the value of volunteering for events over the past few decades [ 35 , 36 ]. For event planners of all sorts, from small-scale to mega-events, sports volunteers are a crucial and valued human resource [ 37 , 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of sponsorship, Self-Determination Theory (SDT) suggests that individuals who feel autonomous and in control are more motivated to seek sponsorships aligned with their personal goals. Additionally, when individuals feel competent in securing sponsorships, they are more likely to engage in effective sponsorship-seeking behaviors [ 35 ]. Regarding expenditure, SDT highlights the importance of autonomy and competence, as individuals who feel autonomous in decision-making and competent in financial management are more likely to make responsible and purposeful choices [ 34 ].…”
Section: Literature Reviewmentioning
confidence: 99%